Analysis of the Jigsaw Learning Model on Pancasila Implementation Material From Time to Time Phase D in the Independent Curriculum - Putri, Liana Anisa; Murdiono, Mukhamad (Al Makki Publisher, 2023)
This study aims to analyze the Jigsaw learning model in the form of a sub-chapter of the material Implementation of Pancasila from Time to Time Phase D in the Independent Curriculum. This research uses the method of literature study or literature review using content analysis to better understand and interpret a study. The results showed a model that is very suitable for use in learning outcomes in the form of subchapters, namely the material Implementation of Pancasila From Time to Time Phase D. The jigsaw model makes students work hand in hand in mastering the material and encourages student activity in order to achieve maximum results. Each member or individual is taught to take responsibility for the submaterial they obtain. Students have independent responsibilities and teach students to communicate well, therefore this model emphasizes the development of civic knowledge citizenship aspects. Then the benefit of this model is to prevent competition and increase collaboration as contained in the independent curriculum.